Enhancing the identity of Malay small town through integrated social space / Zul Azri Abd Aziz, Azrul Bahaluddin and Azran Mansor - Abd Aziz, Zul Azri; Bahaluddin, Azrul; Mansor, Azran (2012)
Social space is a place where people meet and interact within their community. Understanding the concept of social space integration within the context of a small town is essential to prove that the liveliness of the town is important to show the identity of a Malay town. From the literature study, the character of social space is related to the social behaviour and its response to the environment. This is also related to the use of the spaces within the Malay small town. The main purpose of the study is to develop integrated social spaces which focus on community activities as it promotes good sense of place that will enhance the identity of Malay small town. From the historical perspective, the development of the Malay small town is unique in the sense that there is a strong connection between the building environments from different eras. However, there is evidence in which these characters are threatened by the ongoing rapid development around them. Some of the threats come from the public behaviour and authorities who are less concern with the cultural importance of the existing community. This study has identified the potential of social space integration based on the physical aspect as well as the non- physical ones which are essential for the survival of a Malay small town‟s attributes. It is part of the strategy to improve the character of the social spaces in today‟s development context apart from solving the identity crises faced by several small towns as well bringing back the quality of urban society that is slowly deteriorating.